Experimental Immunization Based on Plasmodium Antigens Isolated by Antibody Affinity - Ali N. Kamali; Patricia Marín-García; Isabel G. Azcárate; Antonio Puyet; Amalia Diez; José M. Bautista (Journal of Immunology Research)
Vaccines blocking malaria parasites in the blood-stage diminish mortality and morbidity caused by the disease. Here, we isolated antigens from total parasite proteins by antibody affinity chromatography to test an immunization against lethal malaria infection in a murine model. We used the sera of malaria self-resistant ICR mice to lethal Plasmodium yoelii yoelii 17XL for purification of their IgGs which were subsequently employed to isolate blood-stage parasite antigens that were inoculated to immunize BALB/c mice. The presence of specific antibodies in vaccinated mice serum was studied by immunoblot analysis at different days after vaccination and showed an intensive immune response to a wide range of antigens with molecular weight ranging between 22 and 250 kDa. The humoral response allowed delay of the infection after the inoculation to high lethal doses of P. yoelii yoelii 17XL resulting in a partial protection against malaria disease, although final survival was managed in a low proportion of challenged mice. This approach shows the potential to prevent malaria disease with a set of antigens isolated from blood-stage parasites.